Iran’s Anti-Western Rhetoric as a Sign of Potential Threat to the International Community - Dančo, Ján (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2023)
The aim of this paper is to shed light on some of the views of Iran’s supreme political and spiritual leader on Western countries. The paper is based on information obtained through quantitative content analysis of texts and the method of semi-structured interviews with leading Czech and Slovak experts in the field of the Middle East. A number of research questions can also be defined: What are the Iranian regime’s main accusations against Western countries? To what extent should these statements be taken seriously? Does Iran pose a potential threat to the international community on the basis of this hostile rhetoric? As the analysis shows, although some of these statements are based on a realistic basis, the rest constitute a well thought-out propaganda concept with which the local regime is trying to cover its own shortcomings or to win the favour of the local population. Celem niniejszego opracowania jest rzucenie światła na niektóre poglądy najwyższego politycznego i duchowego przywódcy Iranu dotyczące państw zachodnich. Artykuł opiera się na informacjach uzyskanych dzięki ilościowej analizie treści tekstów oraz metodzie wywiadów półstrukturalnych z czołowymi czeskimi i słowackimi ekspertami w dziedzinie Bliskiego Wschodu. Zdefiniowano następujące pytania badawcze: Jakie są główne zarzuty reżimu irańskiego wobec państw zachodnich?, Na ile należy traktować te wypowiedzi poważnie?, Czy na podstawie tej wrogiej retoryki Iran stanowi potencjalne zagrożenie dla społeczności międzynarodowej? Jak wynika z przeprowadzonej analizy, choć część z tych wypowiedzi oparta jest na realistycznych podstawach, to pozostałe stanowią przemyślaną koncepcję propagandową, za pomocą której tamtejszy reżim stara się przykryć własne niedociągnięcia lub zdobyć przychylność miejscowej ludności.
Antyzachodnia retoryka Iranu jako przejaw potencjalnego zagrożenia dla społeczności międzynarodowej
Keywords: Islamic Republic of Iran; Ali Khamenei; Western countries; foreign affairs; Islamska Republika Iranu; Ali Chamenei; państwa zachodnie; sprawy zagraniczne